2006
DOI: 10.1002/ijc.21736
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative antitumor effects of vitamin D3 derivatives and rosemary preparations in a mouse model of myeloid leukemia

Abstract: 1a,25-dihydroxyvitamin D 3 (1,25D 3 ) is a powerful differentiation agent, which has potential for treatment of myeloid leukemias and other types of cancer, but the calcemia produced by pharmacologically active doses precludes the use of this agent in the clinic. We have shown that carnosic acid, the major rosemary polyphenol, enhances the differentiating and antiproliferative effects of low concentrations of 1,25D 3 in human myeloid leukemia cell lines (HL60, U937). Here we translated these findings to in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 62 publications
2
68
0
Order By: Relevance
“…Currently, CA has been reported to have several properties in antitumor, such as colonic cancer, mammary tumors, as well as skin tumors, through regulating cancer cell growth, apoptosis, reactive oxygen species, and also Akt activation. [16][17][18][19][20] And also, previous studies have suggested that nanoparticulate drug delivery systems have been known to better the bioavailability of drugs on intranasal administration compared with only drug solutions. 21,22 In addition, a study has found that nanoparticulate drug delivery system for CA intranasal administration needed less amounts of administrations to induce the required pharmacological reaction due to its ability to locate on the olfactory mucosal region and supply controlled CA delivery for prolonged time periods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, CA has been reported to have several properties in antitumor, such as colonic cancer, mammary tumors, as well as skin tumors, through regulating cancer cell growth, apoptosis, reactive oxygen species, and also Akt activation. [16][17][18][19][20] And also, previous studies have suggested that nanoparticulate drug delivery systems have been known to better the bioavailability of drugs on intranasal administration compared with only drug solutions. 21,22 In addition, a study has found that nanoparticulate drug delivery system for CA intranasal administration needed less amounts of administrations to induce the required pharmacological reaction due to its ability to locate on the olfactory mucosal region and supply controlled CA delivery for prolonged time periods.…”
Section: Introductionmentioning
confidence: 99%
“…CA has been suggested to have anticancer effects in colon cancer, acute myeloid leukemia, and skin cancer via anti-inflammation, antioxidant, and antimicrobial effects. [15][16][17][18][19][20] However, the molecular mechanism revealing improving liver cancer remains poorly understood. And few previous studies have reported that nanoparticle of CA could be better absorbed for animals.…”
mentioning
confidence: 99%
“…Murine model of myelomonocytic leukemia, WEHI-3B D -cells, were grown in McCoy's 5a medium plus 10% heat-inactivated fetal calf serum (GIBCO-BRL, Gaitherburg, MD) [28]. The cells were passaged and fed with medium 2-3 times per week to maintain the log phase growth.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…The percentage of NSE positive cells in a total of 500 cells was counted using a hemocytometer. Differentiation of WEHI-3B D -cells was determined by the nitroblue tetrazolium (NBT) reduction test, as previously described [28]. To determine the mode of cell death, annexin V and propidium iodide (PI) staining assay was performed (Annexin V-FITC Apoptosis Detection Kit, Sigma).…”
Section: Determination Of Differentiation and Cell Death Markersmentioning
confidence: 99%
“…For example, standard treatment of AML generally includes a synthetic pyrimidine nucleoside cytarabine (Ara-C), which functions as an antimetabolite and DNA polymerase inhibitor, in combination with an anthracycline agent (idarubicin or daunorubicin), which acts as topoisomerase II inhibitor and DNA intercalator [1]. In analogy, the anticancer effects of combinations of vitamin D derivatives (deltanoids) with other agents have been extensively studied in cultures of leukemic cells and other cancer cell types [9,10,11,12], animal models of cancer [13, 14] and clinical trials [15,16,17]. These studies are especially important since combination treatment may allow lower doses of deltanoids, thereby further limiting calcemic toxicity of these compounds.…”
Section: Introductionmentioning
confidence: 99%